Dietary Probiotic Compound Improves Reproductive Performance of Porcine Epidemic Diarrhea Virus-Infected Sows Reared in a Japanese Commercial Swine Farm under Vaccine Control Condition - Inatomi, Takio; Amatatsu, Masaaki; Romero-Pérez, Gustavo A.; Inoue, Ryo; Tsukahara, Takamitsu (Frontiers in Immunology, 2017)
Lactogenic immunity transferred to piglets after inoculation of a live vaccine to pregnant sows was proved limited to control porcine epidemic diarrhoea (PED). Hence, here we evaluated the efficacy of administration of a probiotic compound with Bacillus mesentericus, Clostridium butyricum and Enterococcus faecalis together with a commercial live-attenuated PED vaccine (Nisseiken PED Live Vaccine, Nisseiken, Tokyo, Japan) to improve the health and reproductive performance of PED-infected sows. Twenty pregnant sows in a PED-positive farm were equally divided into probiotics-administered (VP) and control (VC) sows groups. A commercial live-attenuated vaccine was injected as per the manufacturer’s instruction. The probiotic compound (15 g/day) was orally administrated to VP from six weeks pre-parturition to seven days post-parturition (ppd7). VP had a significantly higher body weight at ppd7 than VC (191 kg vs 186 kg; P<0.05). At day 3 post-parturition (ppd3) (4.18 kg/d vs 3.63 kg/d) and ppd7 (5.14 kg/d vs 4.34 kg/d), milk produced by VP was significantly (P<0.05) greater than that by VC. Total IgA and IgG concentrations at day 0 were significantly (P<0.05) higher in whey of VP (1.9 and 6.6 g/dL, respectively) than in that of VC (1.7 and 6.1 g/dL, respectively). However, total IgG concentration in whey of VP and VC at ppd3 and ppd7 did not differ. Antibody titre was significantly higher at day 0 in serum of VP than it was that of VC (60 vs 37 in geometric mean; P<0.05). Likewise, the antibody titre in whey of VP and VC was found to be similar at day 0 (416 vs 208 in geometric mean; P=0.13). Consequently, VP had fewer days between weaning and return to oestrus than did VC (7 vs 10 days; P<0.05). Moreover, piglets of VP had a significantly (P<0.05) higher litter weight at birth (9,252 g/litter) and a lower mortality (12%) during suckling than those of VC (8,686 g/litter and 28%, respectively). In summary, probiotic-supplemented, PED-vaccinated sows were healthier, transferred PED-specific antibodies via colostrum to piglets, had greater litter weight at birth and reduced mortality during suckling.